2000
DOI: 10.1002/1099-0518(20001001)38:19<3451::aid-pola10>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopolymerization

Abstract: The background and summary of the events that led to the discovery and confirmation of an unusual and unexpected mode of polymerization of certain vinyl monomers is presented. Originally, the process was described as an alternating intra‐intermolecular chain propagation mechanism. For convenience and because cyclic structures are introduced into the polymer chain, the term cyclopolymerization has been adopted. Early attempts to determine the relationship of cyclopolymerization to stereochemical control and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
117
0
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 35 publications
2
117
0
8
Order By: Relevance
“…The efficiency and selectivity in the cation recognition by PPEG6DMA was further evaluated in competitive recognition. Thus, in cyclohexanone/ acetone-d 6 (1/1, v/v), the polymer was mixed with an equimolar mixture of Na and another alkali metal cation, and the selectivity was evaluated in monitoring the sodium guest by 23 Na NMR spectroscopy (Fig. 5); obviously, 1 H or 13 C NMR is totally useless in this analysis, because there was little difference in the chemical shift between cyclic PEG units with Na and with another cation.…”
Section: Cationmentioning
confidence: 70%
See 2 more Smart Citations
“…The efficiency and selectivity in the cation recognition by PPEG6DMA was further evaluated in competitive recognition. Thus, in cyclohexanone/ acetone-d 6 (1/1, v/v), the polymer was mixed with an equimolar mixture of Na and another alkali metal cation, and the selectivity was evaluated in monitoring the sodium guest by 23 Na NMR spectroscopy (Fig. 5); obviously, 1 H or 13 C NMR is totally useless in this analysis, because there was little difference in the chemical shift between cyclic PEG units with Na and with another cation.…”
Section: Cationmentioning
confidence: 70%
“…and 40 Hz) and with PPEG3MA (a linear pendant counterpart to PPEG6DMA: -0.34 p.p.m. and 135 Hz), again demonstrating the efficient cation binding by 23 Na NMR.…”
Section: Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] The polymerization of non-conjugated dienes can also be used to synthesize polymers with cycloalkane groups because chain growth is accompanied by monomer ring closure. 12 Early transition metal complexes have been extensively used in cyclopolymerization reactions. [13][14][15][16][17][18][19][20][21][22][23][24] The polymers produced via cyclopolymerization often contain both cis-and trans-isomeric repeating units.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Also, the inclusion of monomers that undergo cyclopolymerization has been investigated. [7] Another approach is the use of expandable monomers. Bailey reported that bicyclic monomers, like the spiroorthocarbonates (SOCs) and the spiroorthoesters undergo expansion during polymerization.…”
Section: Introductionmentioning
confidence: 99%